2013
DOI: 10.1371/journal.pone.0052554
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning of Tissues' Viscosity and Surface Tension through Contractility Suggests a New Role for α-Catenin

Abstract: What governs tissue organization and movement? If molecular and genetic approaches are able to give some answers on these issues, more and more works are now giving a real importance to mechanics as a key component eventually triggering further signaling events. We chose embryonic cell aggregates as model systems for tissue organization and movement in order to investigate the origin of some mechanical constraints arising from cells organization. Steinberg et al. proposed a long time ago an analogy between liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
84
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 49 publications
9
84
0
1
Order By: Relevance
“…Our results suggest that cadherin reduces tension at cell contacts through a downregulation of cortex thickness or density (Clark et al, 2013), with the residual cortex being sufficient for cadherin anchoring (Maître et al, 2012). Such a catalytic role of cadherins in adhesion can be mediated by α-catenin (Stirbat et al, 2013). It is the reduced tension β* at contacts that becomes relevant in the following section for the calculation of tissue viscosity (see Fig.…”
Section: Box 1 Cell Adhesion and Cortical Tensionsmentioning
confidence: 77%
See 1 more Smart Citation
“…Our results suggest that cadherin reduces tension at cell contacts through a downregulation of cortex thickness or density (Clark et al, 2013), with the residual cortex being sufficient for cadherin anchoring (Maître et al, 2012). Such a catalytic role of cadherins in adhesion can be mediated by α-catenin (Stirbat et al, 2013). It is the reduced tension β* at contacts that becomes relevant in the following section for the calculation of tissue viscosity (see Fig.…”
Section: Box 1 Cell Adhesion and Cortical Tensionsmentioning
confidence: 77%
“…To quantitate cell contact fluctuation, contact lengths were measured at 1 min intervals in time-lapse recordings of explants filmed under indirect illumination. Contact angles between cells were measured in cell pairs or at the periphery of tissue explants (Stirbat et al, 2013) fixed and fractured after rounding up for 0.5-1 h. All measurements used the Carl Zeiss Axiovision program; accuracy was ±0.2°(s.d. ; n=54) for angles, ±0.28 µm (s.d.…”
Section: Measurements Of Cell and Tissue Parametersmentioning
confidence: 99%
“…More recently, however, experimental findings (Krieg et al, 2008) and theoretical considerations (Brodland and Chen, 2000;Manning et al, 2010) rehabilitated Harris' original conjecture with a modification -instead of treating contractility as an alternative mechanism, it is described to act together with adhesion to determine the mutual attachment of cells. A further, crucial challenge to our conventional concept of adhesion came with the recognition that the binding energies of adhesion molecules are too small to account for the observed degrees of cell-cell attachment (Youssef et al, 2011;Maître et al, 2012;Amack and Manning, 2012;Stirbat et al, 2013;David et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that the efficiency of medical drugs tested on 2D cell culture systems is not transposable to 3D in more than 50% cases (12). Recently, 3D cellular aggregates have been identified as a model system that approximates living tissues and tumors (13)(14)(15). Cell aggregates in culture consist of hundreds to thousands of cells.…”
mentioning
confidence: 99%
“…However, contrary to foam, which is solid, cell aggregates flow like a liquid when placed onto an adhesive surface or in contact with each other. For example, cell aggregates in solution form spheroids to minimize their surface energy, and fuse when in contact with each other like liquid droplets (15). Since the pioneering work by Steinberg in the 1960s (17), several studies have shown that the mechanical behavior of tissues and cellular aggregates can be characterized through their liquid-like behavior (18,19).…”
mentioning
confidence: 99%